Translation and cognition - Shreve, Gregory M., 1950-; Angelone, Erik (American Translators Association scholarly monograph series ;, 2010)
Translation and Cognition assesses the state of the art in cognitive translation and interpreting studies by examining three important trends: methodological innovation, the evolution of research design, and the continuing integration of translation process research results with the core findings of the cognitive sciences. Several of the volume's essays focus on fruitful new process research methods, such as eye tracking and keystroke logging that have arisen to supplement the use of think-aloud protocols. Another set of contributions investigates how some central theories, concepts, and metho.